(3ELGHI Ydi SDGds - (3GdLfRj , YeQ Hf YKeGf Hf GdMSjf Hf TYjH, CHh MaU,J (B550 (3g` s
(3ChdgG (B:s
(3ai Cf GdhGh GdhGhai bhdg hEf cGfhG ddMGd hEf ai bGd GfgG ddYWa s
(3BNQgG (B:s
(3hdG NdGa Cf Ef hCNhGJgG dG JONd Ydi GdeHJOC aGfJgi cdGeg Ke s
(3Vef eLehY , JQJjHgG (B: (3GdQGHY hGdYTQhfs
(3GfXQ GdeNWhW Qbe (B292s
(3HgG fXGe GdJYbjHIs
(3SCd GdSDGd LGQ Gddg GdReNTQis
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B296s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdfMhs